The shifting sands of the North Sea lowlands - Ritson, Katie, author.
1 online resource
Keywords: Global seawater levels are rising and the low-lying coasts of the North Sea basin are amongst the most vulnerable in Europe. In our current moment of environmental crisis, the North Sea coasts are literary arenas in which the challenges and concerns of the Anthropocene are being played out. This book shows how the fragile landscapes around the North Sea have served as bellwethers for environmental concern both now and in the recent past. It looks at literary sources drawn from the countries around the North Sea (Denmark, Germany, the Netherlands, and England) from the mid-nineteenth century onwards, taking them out of their established national and cultural contexts and reframing them in the light of human concern with fast-changing and hazardous environments. The six chapters serve as literary case studies that highlight memories of flood disaster and recovery, attempts to engineer the landscape into submission, perceptions of the landscape as both local and global, and the imagination of the future of our planet. This approach, which combines environmental history and ecocriticism, shows the importance of cultural artefacts in understandings of, and responses to, environmental change, and advocates for the importance of literary studies in the environmental humanities. This book will be of great interest to students and scholars of the Environmental Humanities, including Eco-criticism and Environmental History, as well as anyone studying literature from the Germanic philologies.